EFFICENCY ASSESMENT MODEL OF BASIC LEVERAGE TECHNIQUE PERFORMANCE WITHIN PROGRAM OF SPECIAL PHYSICAL EDUCATION - Ranko Baltić; Đurica Amanović; Milija Ljubisavljević; Stipe Blažević; Žarko Kostovski (Sport Scientific And Practical Aspects, 2025)
The main objective of this study was to determine the structure of morphological and motor features of students in the first year of studies and their impact on the efficiency of mastering curriculum of Special Physical Education in the part referring leverage. For the purposes of this study we used a battery of tests which included a set of twenty morphological, seven motor and seven criterion variables representing basic leverage techniques from SPE program. The study was conducted on a sample of eighty two respondents. Descriptive, correlation and factor analysis were conducted on all variables and accordingly can be determined that the analyzed data are reliable and can be validly interpreted. Qualitative analysis applying confirmative techniques, made it possible to define efficiency assessment model of basic leverage technique performance. On a practical level, the research results will contribute to a better selection and optimization in choosing means and methods in procedures in order to improve motor efficiency of each individual.